Evaluasi Proses Bisnis Menggunakan Metode Quality Evaluation Framework (QEF) (Studi Kasus Bidang Akreditasi Dan Aim Pusat Jaminan Mutu Universitas Brawijaya) - Noval Ageng Siswanto; Aditya Rachmadi; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Pusat Jaminan Mutu (PJM) is an institution under the auspices of the rector with the objective of ensuring the quality of management system, research, and implementation of education in University of Brawijaya. Quality assurance at PJM is Audit Internal Mutu (AIM) and Accreditation, but in each case there are complaints received by stakeholders. Complaints received are among the activities of the use of auditing systems that are less than the maximum, late report activity, and implementation monitoring program that is not appropriate. From several complaints that have been accepted then the required evaluation of the activities that are divided on the factors of service quality. It is therefore necessary to evaluate the current business process using the Quality Evaluation Framework (QEF). Business process evaluation is done by modeling the current business process first using Business Process Model and Notation (BPMN). Determining the quality factor along with the goal is applied to each indicator of success in business poses, then calculation of target realization is done. The result of calculation has been done and got quality factor that is not in accordance with the target. Quality factors are not suitable will be done root cause analysis by using the technique fishbone diagram and 5 whys.